GESTION DE L’EQUIPE DE TRAVAIL ET EXERCICE DE L’AUTORITE CHEZ LES FEMMES CADRES SUPERIEURES - Koua N’da Lazare (European Scientific Journal, ESJ, 2012)
This study deals with senior management women face to some factors as the adhesion of the work team and authority practice, the perception of their position in the hierarchy and daily conflicts management, the competence and authority practice. The study, show us in first time that senior management women are not affected in their authority practice when they are confronted with difficulties to obtain the adhesion of their work team. Secondly, we notice that senior management women think that they should have been out of daily conflicts if they haven’t been at the first position (manager of the work team). At least we notice that these kinds of women are obliged to demonstrate frequently their competence to reinforce their authority.